Analisis Pengaruh Harga, Citra Merek, dan Kredibilitas Perusahaan terhadap Niat Membeli Konsumen pada Produk Kawasaki di Kota Yogyakarta - Pamuji Hari Santoso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The low sales of Kawasaki motorcycles in comparison with its competitors leads to further analysis of the factors that influence it. This study aims to determine the effect of price, brand image, and the credibility of the company to purchase intentions. The population in this study is the entire population or people who live in the region of Yogyakarta. Convenience sampling is the researchers choice in sampling. For data collection, the authors disseminate 250 questionnaires to the respondents, but only 217 data is feasible to use. The analytical tool used is the test of validity and reliability, multiple regression, classical assumptions and double determination. The results show that there is influence of price, brand image and credibility of the company towards consumers purchase intention on Kawasaki products in Yogyakarta city. Keywords: Price, Brand Image, Corporate Credibility, and Intention to Buy